TRIPUSAT PENDIDIKAN ISLAM YANG INTEGRATIF DALAM PENGEMBANGAN PROGRAM PENDIDIKAN ISLAM DI SEKOLA - Zainul Huda; Ahmadi M (Fakultas Tarbiyah, Universitas Ibrahimy, 2019)
The responsibility of Islamic education cannot be carried out unilaterally. Ki Hajar Dewantara stated that it requires the cooperation of three components which called as tripusat pendidikan (center of three in education), they are families, educational institutions, and society. Those three components are one unit and complement each other in realizing educational goals. No matter how good the curriculum in madrasah (school), it was not be optimal if do not supported by family and society and otherwise. Therefore student failure is the fault of all components, not just the fault of educational institutions or teachers.